2014
DOI: 10.1111/tri.12375
|View full text |Cite
|
Sign up to set email alerts
|

CNI withdrawal for post-transplant lymphoproliferative disorders in kidney transplant is an independent risk factor for graft failure and mortality

Abstract: SummaryPost-transplantation lymphoproliferative disorders (PTLD) are associated with poor patient and graft survival. The risk of rejection and subsequent graft loss are increased by the reduction of immunosuppression therapy, the cornerstone of PTLD treatment. This multicentre, retrospective, nonrandomized cohort study includes 104 adults who developed PTLD after renal or simultaneous renal/pancreatic transplantation between 1990 and 2007. It examines the effect of calcineurin inhibitor (CNI) withdrawal on lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 38 publications
3
20
0
1
Order By: Relevance
“…Our overall survival rates after PTLD diagnosis were similar or better compared with previously reported rates . Although the size of the population involved makes it difficult to draw firm conclusions, a shorter therapeutic delay is probably more significant in PTLD compared with sporadic lymphoproliferative disorders in immunocompetent patients, as reduction in immunosuppression should be instituted immediately at the mere suspicion of PTLD, while the need for further investigation is evaluated.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our overall survival rates after PTLD diagnosis were similar or better compared with previously reported rates . Although the size of the population involved makes it difficult to draw firm conclusions, a shorter therapeutic delay is probably more significant in PTLD compared with sporadic lymphoproliferative disorders in immunocompetent patients, as reduction in immunosuppression should be instituted immediately at the mere suspicion of PTLD, while the need for further investigation is evaluated.…”
Section: Discussionsupporting
confidence: 77%
“…The risk following kidney transplantation (often poorly defined) varies between 1 and 3% , although it has been reported up to 7% . PTLD development is associated with decreased survival of both patients and grafts , 5‐year patient survival after diagnosis ranging between 37 and 65% .…”
Section: Introductionmentioning
confidence: 99%
“…CLAD (mostly BOS) indeed mainly developed following prior early‐onset PTLD, suggesting that reduction of immunosuppression shortly after LTx may be the culprit for subsequent CLAD development. Similar findings were demonstrated in renal transplantation, where calcineurin‐inhibitor withdrawal for PTLD was independently associated with reduced graft and patient survival . In a minority of patients CLAD preceded PTLD, which demonstrated to be almost exclusively late‐onset PTLD cases.…”
Section: Discussionsupporting
confidence: 76%
“…13 was already in a state of brain‐death after the surgery; therefore overly stressful chemotherapy was not performed. Meanwhile, graft survival following late‐onset PTLD appeared to be poorer than that in previous studies . IR is commonly performed as an initial treatment for PTLD because impairment of the immunological system is a major trigger of PTLD, although the rejection caused by reduction of immunosuppressive conditions remains an unresolved problem.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, some patients who received IR suffered from graft loss in the present study. Rabot et al reported that calcineurin inhibitor withdrawal could adversely influence graft and patient survival . Meanwhile, RTX and CHOP chemotherapy can be effective for maintaining graft function .…”
Section: Discussionmentioning
confidence: 99%